Space-time ripples - Jankovič, Taj (Matrika, 2017)
Recent first direct detection of gravitational waves opened a new window on the universe. Gravitational waves arise from small perturbations of space-time and from their characteristics it is possible to determine properties of astrophysical objects from which they originate. In this seminar Einstein equation is introduced to describe gravitational waves and ascertain their properties. Furthermore, possible astrophysical sources are presented, as well as the first directly and indirectly detected event.
Keywords: astrofizika; astrophysics; gravitacija; gravitacijski valovi; gravitation; gravitational waves; teorija relativnosti; theory of relativity